Numerical simulation of the impact and freezing stage of supercooled droplets on the ship superstructure surface in the Arctic route - Bai, Xu; Yang, Sujie; Wei, Ping; Zhou, Li (Frontiers in Energy Research, 2022)
Icing is not only affect the stability and safety of Arctic navigation ships, but also damage the facilities on board and endanger the safety of personnel. The icing result of ship surface is closely related to the icing process of water droplets on the surface. In the icing process of supercooled water droplets colliding with the ship surface, the impact and icing are coupled with each other. This process is extremely sensitive. The final ice type and physical parameters will change due to external disturbance. Therefore, in order to obtain accurate ship icing results, the micro impact icing process of water droplets on the surface needs to be considered. From the microscopic point of view, using the numerical simulation method of solidification/melting model in fluent, this paper analyzes the effects of undercooling, contact angle and droplet impact on the microscopic solidification process of supercooled droplets, the results show that :1) Droplet impact will affect droplet volume; 2) When the impact velocity increases, the freezing time decreases; 3) In the case of the same impact velocity, the freezing time and cooling time vary very closely even if the degree of undercooling and contact angle are different.